Variations in T cell transcription factor gene structure and expression associated with the two disease forms of sheep paratuberculosis. (December 2016) - Nicol, Louise; Wilkie, Hazel; Gossner, Anton; Watkins, Craig; Dalziel, Robert; Hopkins, John
Abstract Two different forms of clinical paratuberculosis in sheep are recognised, related to the level of bacterial colonization. Paucibacillary lesions are largely composed of lymphocytes with few bacteria, and multibacillary pathology is characterized by heavily-infected macrophages. Analysis of cytokine transcripts has shown that inflammatory Th1/Th17 T cells are associated with development of paucibacillary pathology and Th2 cytokines are correlated with multibacillary disease. The master regulator T cell transcription factorsTBX21, GATA3, RORC2 andRORA are critical for the development of these T cell subsets. Sequence variations of the transcription factors have also been implicated in the distinct disease forms of human mycobacterial and gastrointestinal inflammatory diseases. Relative RT-qPCR was used to compare expression levels of each transcript variant of the master regulators in the ileo-caecal lymph nodes of uninfected controls and sheep with defined paucibacillary and multibacillary pathology. Low levels ofGATA3 in multibacillary sheep failed to confirm that multibacillary paratuberculosis is caused simply by a Th2 immune response. However, high levels ofTBX21, RORC2 andRORC2v1 highlights the role of Th1 and Th17 activation in paucibacillary disease. IncreasedRORAv1 levels in paucibacillary tissue suggests a role for RORα in Th17 development in sheep; while elevated levels ofRORAv4 hints that this variant might inhibit RORα function and depress Th17 development in multibacillary sheep.